(untitled) (Research, Society and Development, 2021)
Some of the pacients affected by COVID-19 present thrombi. The objective of this study was to assess the association between comorbidities of COVID-19 and thrombi in the lungs. Articles with the descriptors “Pathology”, “Autopsy”, “COVID-19”, “SARS-CoV-2” were extracted from the databases: Medical Literature Analysis and Retrieval System Online (MEDLINE/PUBMED), Cochrane Library, Virtual Health Library (VHL), Web of Science and Scopus. Eligibility criteria were: articles in English, published between January 1 and May 28, 2020, with confirmed cases of COVID-19, with description of necropsy and analysis pulmonary histopathological. The data were tabulated: age, sex, comorbidities, time of disease evolution and macro and microscopic findings of the lungs. Twenty articles were included, totaling 119 necropsies, most of them original articles or case reports Regarding gender, 86 were male, 23 female and 10 were undetermined. Seventy-five of the individuals included had thrombi in the lungs, among these, 98.7% had diffuse alveolar damage (DAD). male or that patients with hypertension, diabetes or deep vein thrombosis (DVT) were more likely to have thrombi in their lungs. Approximately 70% of the analyzed patients were between 60 and 89 years old. The average length of hospital stay was 6.4 days. In 90.7% of the pulmonary histological samples, aspects of DAD were identified. Of the macroscopic findings of the lungs, the most prevalent was “heavy lungs”, of which 92.1% had thrombi. Hospitalized patients have a greater chance of dying within the 9th day of hospitalization. The work identified cases of thrombi in the lungs more frequently in individuals with DVT, diabetes and hypertension.